Hagenia from the early Miocene of Ethiopia: Evidence for possible niche evolution?. Issue 10 (23rd March 2021) - Grímsson, Friðgeir; Ulrich, Silvia; Coiro, Mario; Graham, Shirley A.; Jacobs, Bonnie F.; Currano, Ellen D.; Xafis, Alexandros; Zetter, Reinhard
Abstract: Fossil pollen believed to be related to extant Hagenia abyssinica were discovered in the early Miocene (21.73 Ma) Mush Valley paleoflora, Ethiopia, Africa. Both the fossil and extant pollen grains of H. abyssinica were examined with combined light microscopy, scanning electron microscopy, and transmission electron microscopy to compare the pollen and establish their relationships. Based on this, the fossil pollen grains were attributed to Hagenia . The presence of Hagenia in the fossil assemblage raises the questions if its habitat has changed over time, and if the plants are/were wind pollinated. To shed light on these questions, the morphology of extant anthers was also studied, revealing specialized hairs inside the anthers, believed to aid in insect pollination. Pollen and anther morphology are discussed in relation to the age and origin of the genus within a molecular dated phylogenetic framework, the establishment of complex topography in East Africa, other evidence regarding pollination modes, and the palynological record. The evidence presented herein, and compiled from the literature, suggests that Hagenia was an insect‐pollinated lowland rainforest element during the early Miocene of the Mush Valley. The current Afromontane habitat and ambophilous (insect and wind) pollination must have evolved in post‐mid‐Miocene times. Abstract : This study shows that modern counterparts of fossil taxa might not be ideal to infer ecological or environmental traits, such as pollination, elevation, temperature, and precipitation on fossil plants or their assemblages. It is clear that since the origin of Hagenia its ecological requirements have changed significantly.